Guillain–Barre syndrome and link with COVID-19 infection and vaccination: a review of literature - Valaparla, Vijaya Lakshmi; Rane, Schweta P.; Patel, Chilvana; Li, Xiangping (Frontiers in Neurology, 2024)
Background: Guillain Barré Syndrome (GBS) is an autoimmune disease associated with significant morbidity. A wide variety of infectious and non-infectious triggers have been identified in association with GBS. Covid 19 has gained attention in recent years for its role in GBS pathogenesis. Our study aimed at reviewing the literature on GBS and its epidemiological and pathophysiological association with Covid 19.Description : Recent literature on GBS associated with Covid 19 infection in the form of case reports, case series, systematic reviews and large-scale epidemiological studies were reviewed. We also reviewed studies that included vaccines against Covid 19 in association with GBS. Studies that focused on understanding the pathobiology of GBS and its link with infectious agents including Covid 19 were reviewed.Despite lack of consensus, GBS is strongly associated with Covid 19 infection. The exact pathophysiological mechanism of Covid 19 as a causative agent of GBS is unknown. Mechanisms like proinflammatory state, triggering autoimmunity and direct viral invasion are postulated and remain investigational. Adenovirus vector vaccines are most likely associated with GBS, and the consensual reports clearly suggest mRNA vaccines are associated with low risk and may be protective against GBS by reducing the risk of Covid infection.